2012
DOI: 10.2217/fnl.12.25
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Region-Dependent Neuroinflammation, Nmda Receptor Loss and Atrophy In An Animal Model of Penetrating Brain Injury

Abstract: Dynamic changes in neuroinflammation and glutamate NMDA receptors (NMDAR) have been noted in traumatic and ischemic brain injury. Aim Here we investigate the time course and regional distribution of these changes and their relationship with atrophy in a rat model of penetrating brain injury. Materials & methods Quantitative autoradiography, with the neuroinflammation marker [3H]PK11195 and the NMDAR antagonist [125I]iodoMK801, was performed on brains of animals subjected to a unilateral wireknife injury at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…These findings align with previous reports on irradiation induced neuro-inflammation and the ability of neuro-inflammation to spread from the site of injury to relatively remote regions of the central nervous system [ 36 , 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…These findings align with previous reports on irradiation induced neuro-inflammation and the ability of neuro-inflammation to spread from the site of injury to relatively remote regions of the central nervous system [ 36 , 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…Research concerning TSPO ligand uptake in animal models of TBI overwhelmingly supports the findings of its role as a microglia/macrophage activator. Specifically, studies have revealed that the increases of BP using 11C-PK11195 can be associated with both the time and type of brain injury [174][175][176]. Investigations using second-generation ligands fully support the results of the increased uptake in different types of trauma but are in contrast with the findings of increases of TSPO expression early after traumatic events [50].…”
Section: Tspo and Traumatic Brain Injuries (Tbis)mentioning
confidence: 96%
“…In this study we examined cellular mechanisms of the positive motor effect of intrastriatally injected BoNT-A by [ 18 F]fallypride PET/CT scans in hemi-PD rats, as BoNT-A was previously demonstrated to abolish apomorphine-induced rotational behavior in 6-OHDA-lesioned [ 23 , 24 , 25 , 26 ]. The control group respected the entire surgical procedure as the minimal lesion caused by the insertion of the syringe could lead to changes in receptor binding sites [ 32 , 33 ]. We did not include an experimental group studying BoNT-A in sham-lesioned rats in our design as we assumed that BoNT-A would not alter per se the expression of D 2 /D 3 receptors.…”
Section: Discussionmentioning
confidence: 99%